Research on the Evolutionary Game Model and Stable Strategy of Urban Management Law Enforcement - Fangkun Xin; Zijing Wang (Complexity)
As a form of the informal economy, countries around the world have different policies towards street vendors. This paper constructs a law enforcement game model composed of the Chengguan, street vendors, and urban residents in China. Based on the evolutionary game theory, we achieved the evolutionary stable equilibrium points under complying with different constraint conditions by solving the replicator dynamic equations of parties in the dynamic system. Through the gradual stability analysis of the equilibrium point, the stable strategy of the evolutionary game can be calculated. It is found that the flexible law enforcement behavior of urban management departments plays an important leading role in urban street governance. Flexible law enforcement not only requires macro policy arrangements but also tests the executive wisdom of street bureaucrats.